2012
DOI: 10.1093/jrr/rrs002
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-148b enhances the radiosensitivity of non-Hodgkin's Lymphoma cells by promoting radiation-induced apoptosis

Abstract: Growing evidence has demonstrated that microRNAs (miRNAs) play an important role in regulating cellular radiosensitivity. This study aimed to explore the role of miRNAs in non-Hodgkin's lymphoma (NHL) radiosensitivity. Microarray was employed to compare the miRNA expression profiles in B cell lymphoma cell line Raji before and after a 2-Gy dose of radiation. A total of 20 differentially expressed miRNAs were identified including 10 up-regulated and 10 down-regulated (defined as P < 0.05). Among the differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 36 publications
4
35
0
Order By: Relevance
“…Induction of apoptosis, possibly mediated by inactivation of the PI3K-Akt pathway, can also be a result of miR-126 overexpression, and lead to enhanced radiosensitivity (22). In an irradiated non-Hodgkin's lymphoma cell line, miR-148b has been found to increase radiosensitivity of cells (67). In this context, radiation-induced apoptosis through repression of DNA methyltransferase 3b (DNMT3b) is a possible underlying mechanism (67).…”
Section: Mirnas Regulating Relevant Cellular Signaling Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Induction of apoptosis, possibly mediated by inactivation of the PI3K-Akt pathway, can also be a result of miR-126 overexpression, and lead to enhanced radiosensitivity (22). In an irradiated non-Hodgkin's lymphoma cell line, miR-148b has been found to increase radiosensitivity of cells (67). In this context, radiation-induced apoptosis through repression of DNA methyltransferase 3b (DNMT3b) is a possible underlying mechanism (67).…”
Section: Mirnas Regulating Relevant Cellular Signaling Pathwaysmentioning
confidence: 99%
“…In an irradiated non-Hodgkin's lymphoma cell line, miR-148b has been found to increase radiosensitivity of cells (67). In this context, radiation-induced apoptosis through repression of DNA methyltransferase 3b (DNMT3b) is a possible underlying mechanism (67). In addition, miR-181a targets another pro-apoptotic gene, PRKCD (protein kinase C delta type) and contributes to radioresistance by negative regulation of PRKCD expression and inhibition of radiation-induced apoptosis in cervical cancer cell lines (12).…”
Section: Mirnas Regulating Relevant Cellular Signaling Pathwaysmentioning
confidence: 99%
“…As an example, miR-148b is induced by IR in non-Hodgkin's lymphoma, but repressed by IR in endothelial cells (139,152), demonstrating the variability in IR-induced expression changes. It is interesting to note that miRNA expression changes were not always consistent within a single cell line, specifically with regard to IR dose and recovery time post-IR.…”
Section: Ir Affects Mirna Expressionmentioning
confidence: 99%
“…Modulation of specific miRNAs reveals they can have both pro- and anti-survival functions following exposure to radiation. Wu et al found that miR-148b expression was increased after radiation and enhanced the radiosensitivity of Non-Hodgkin Lymphoma cells by promoting apoptosis [21]. Similarly, the overexpression of let-7a decreased K-Ras expression and radiosensitized lung cancer cells [22], whilst increased miR-521 expression sensitized prostate cancer cells to radiation treatment through the regulation of the DNA repair protein CSA [16].…”
Section: Introductionmentioning
confidence: 99%